1986
DOI: 10.1111/j.1365-2125.1986.tb02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Action of compounds with effective in vivo mineralocorticoid activity on ion transport in leucocytes.

Abstract: We have studied the in vitro short‐term effects of aldosterone (1.0‐ 1000 nmol l‐1), cortisol (0.5‐5.0 mumol l‐1), fludrocortisone (1.0‐10 nmol l‐1) and carbenoxolone (0.5‐3 mmol l‐1) on 86rubidium influx (a model for potassium), 22sodium efflux, and [3H]‐ouabain binding capacity in intact human leucocytes. No effect of aldosterone (at concentrations present in Conn's syndrome) or fludrocortisone could be demonstrated on cation fluxes or [3H]‐ouabain binding compared to controls. No significant effect of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although CBX produces a marked increase in rectal transmucosal electrical potential difference [25] (an index of mineralocorticoid activity on the rectum), there is no gastrointestinal potassium loss to account for the hypokalaemia [26]. More recently CBX has been shown to stimulate cellular Na+/ K+-adenosine triphosphatase [27] and it is suggested that the hypokalaemia is simply a 'redistribution hypokalaemia' with no nett change in total body potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Although CBX produces a marked increase in rectal transmucosal electrical potential difference [25] (an index of mineralocorticoid activity on the rectum), there is no gastrointestinal potassium loss to account for the hypokalaemia [26]. More recently CBX has been shown to stimulate cellular Na+/ K+-adenosine triphosphatase [27] and it is suggested that the hypokalaemia is simply a 'redistribution hypokalaemia' with no nett change in total body potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Cx has been found to have effects on ion transport in leukocytes that are independent of those of either mineralocorticoids or glucocorticoids. 36 Placental regulation of the ionic content of amniotic fluid, particularly of sodium and potassium, has been implicated in blood pressure programming in SHR 37 and might be important in genetically normotensive animals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in rats, carbenoxolone has been shown to produce a kaliuresis (Souness & Morns, 1989) and in uitro had no effect on the conversion of 1 I-dehydrocorticosterone to corticosterone at concentrations which markedly inhibit the dehydrogenase reaction . Possible explanations for these differences may be provided by the observations that in rats carbenoxolone potentiated the actions of other natural and synthetic corticosteroids which do not have an 1 1-hydroxyl group and therefore are not metabolized by 11B-OHSD (Morris & Souness, 1990;Funder et al, 1990), and had direct effects on membrane electrolyte transport independent of the presence of corticosteroids (Baron & Green, 1986).…”
Section: Cllnical Significance Of 11p-ohsdmentioning
confidence: 99%